2003
DOI: 10.1074/jbc.m305607200
|View full text |Cite
|
Sign up to set email alerts
|

C5a Receptor Oligomerization

Abstract: Recent studies demonstrate that members of the superfamily of G protein-coupled receptors (GPCRs) form oligomers both in vitro and in vivo. The mechanisms by which GPCRs oligomerize and the roles of accessory proteins in this process are not well understood. We G protein-coupled receptors (GPCRs) 1 are a diverse superfamily of receptors that mediate numerous physiological effects in response to sensory, hormonal, and neurotransmitter stimuli (1). There is mounting evidence that GPCRs can associate as homo-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…The ability of C5aR to cross-link in the absence of peripheral membrane proteins argues that the oligomerization that we observe is a receptorautonomous process. Moreover, we demonstrated that urea treatment had little effect on the ability of C5aR molecules to FRET in yeast (57).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The ability of C5aR to cross-link in the absence of peripheral membrane proteins argues that the oligomerization that we observe is a receptorautonomous process. Moreover, we demonstrated that urea treatment had little effect on the ability of C5aR molecules to FRET in yeast (57).…”
Section: Resultsmentioning
confidence: 87%
“…Heterodimerization of opioid receptors and ␦ results in novel ligand binding and function, proving that GPCR oligomerization has physiologic relevance (12). More recently, energy transfer studies, using either fluorescence (FRET) or bioluminescence (BRET), have also shown the proximity of monomers of many members of the rhodopsin family of GPCRs, including ␤ 2 -adrenergic receptor (13), somatostatin receptors (14), opioid receptors (15), and the C5a receptor (57).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…tors when co-expressed in yeast (60). Accordingly, we suggest that GXXXG-like motifs may be able to direct the formation of specific GPCR complexes as follows.…”
Section: ␣-Factor Receptor Oligomerization Biogenesis and Signalingmentioning
confidence: 90%
“…Heterologous expression systems have provided a variety of answers concerning ligand-dependent regulation of GPCR oligomeric states. Ligand binding, depending on the GPCR studied, can promote (3)(4)(5)(6)(7)(8)(9)(10) or inhibit (11)(12)(13) dimer formation, as well as having no effect on preexisting constitutive homo-or heterodimers (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The fact that heterodimerization may alter the pharmacological properties of a GPCR along with its internalization and signal transduction behavior is of critical importance (26,27).…”
mentioning
confidence: 99%